Estimating Final Grain Yields Using Primordial Leaf Area in Ten Kenyan Hybrid Maize - Serrem , Cornelius K.; Mbingo , J. M. Mbingo (African Journal of Education,Science and Technology (AJEST), 2017)
A study was carried out to evaluate initial leaf area as an indicator of final grain yield for selected Kenyan long and short rain hybrid maize varieties. The project was carried out at Moi university Chepkoilel campus farm in two phases, in the field and in the greenhouse using a completely randomized design. Data collection included primodial leaf destructive collection in the greenhouse and the final grain yield in the field. The key parameters were leaf area index, cob length and weight of threshed grains. Results showed that there was significant difference between varieties (p=0.05). The final grain yield was significant and positively related to the primordial leaf area with an r=0.85 at p=0.05 having the following relationship; GY=1.50LA+1.47; where GY=grain yield, LA=leaf area and r=correlation. There was also a significant and positive correlation between grain yield, and the other dependent variables which included length and circumference of cob before and after threshing, number of rows per cob and number of grains per row. Based on this study, the regression and correlation of the primordial leaf area can be used to predict final grain yield, which has proved to be a useful selection criteria for high yield varieties of Kenyan hybrid maize